Assessing the relationship between climate change anxiety, ecological coping, and pro-environmental behavior: Evidence from Gen Z Bangladeshis - Fariea Bakul; Eamin Zahan Heanoy; Antara Das Antu; Faria Khandakar; Shahin Ahmed (Acta Psychologica)
Climate change has been speculated to cause frequent, long-lasting, and adverse weather events and would affect people's lives-and-well-being. Bangladesh, a low-lying delta is vulnerable to climate change, experiencing natural disasters each year with physical, mental, and economical impact on the population. The primary objective of the present study was to investigate the relationship between climate change anxiety (CCA), climate change-related coping strategies, and pro-environmental behavior (PEB) among Gen-Z Bangladeshis. The secondary objective was to assess CCA level and its associated coping approach among different disaster types witnessed by the respondents, and in disaster-affected vs. non-affected group. A total 557 participants between 18– and 25 years old participated in a cross-sectional survey including 13-items CCA Scale (CCAS), 15-items Ecological Coping Scale (ECS), demographics, and PEB questions. Results demonstrated that functional-impairment subscale and cognitive-impairment subscale of CCAS, MFC (meaning-focused coping), denial, and problem-focused coping (PFC) subscale of ECS, and PEBs were reliably correlated to varying degrees. Moreover, the disaster-affected group had significantly higher cognitive-impairment, functional-impairment, denial, and PFC use than non-affected group. Also, flood-witnessed people demonstrated more cognitive-impaired, functional-impaired, and used more MFC and PFC than storm and drought witnessed people. These findings highlight the awareness level of climate change impact among Gen-Z Bangladeshis, assisting professionals to formulate a tailored intervention.